Development and Validation of a UV Spectrophotometric Method for Almotriptan Malate Estimation in Bulk and Niosomal Formulation - Sulakude, Shweta; Shirkoli, Nisha (International Journal of Pharmaceutical Investigation, 2025)
Background Almotriptan Malate is a selective serotonin receptor agonist developed for migraine management in adults. Its bioavailability is 69.1%, with an elimination half-life of 3 hours and has low aqueous solubility. This study aims to develop a UV spectrophotometric method for Almotriptan Malate and Niosomal formulations, for determining concentration of Active Pharmaceutical Ingredient (API) in drug products. Materials and Methods A combination of 50% ethanol and phosphate buffer pH 6.8 was used as a solvent system. A UV spectrophotometric method was developed, identifying Almotriptan Malate’s absorption peak (λmax) at 227 nm. The method was validated for precision, accuracy, and linearity using calibration curves. The limit of detection and quantification were used to determine sensitivity of the method. Precision, ruggedness and robustness were assessed using Relative Standard Deviation (RSD). Niosomes were prepared using ethanol injection, and particle size and zeta potential were measured to evaluate their self-assembly properties. Results and Discussion The UV spectrophotometric method displayed a strong linear calibration curve, with regression coefficient 0.9974 confirming its reliability for Almotriptan Malate estimation. The LOD and LOQ were satisfactory and the study indicated a percentage RSD below 2% for precision analysis. Robustness tests showed that the method remained stable under different conditions. Niosomal formulations had a particle size of 148.3 nm and a zeta potential indicating strong stability. The percentage yield that was obtained by drug entrapment efficiency was 82.80 % therefore endorsing the Niosomal system as quite effective for Almotriptan Malate drug delivery. Conclusion The developed UV spectrophotometric method is accurate, precise, and reproducible for the estimation of Almotriptan Malate in bulk and Niosomal formulations.
Keywords: Almotriptan Malate; UV-spectroscopic method validation; ICH guidelines